Stories from the field # 1 - Conservation International (Washington, D.C. Conservation International, 1992)
Highlights some of the conservation activities undertaken by Conservation International's conservationists and scientists.
Um grito pela vida=A cry for life (10 min.), Brazil, c1991 -- Una labora silenciosa=A silent work (6 min.), Bolivia, c1992 -- Gente de la Amistad=People of la Amistad (4 min.), Costa Rica.
VHS.
[Music by] Egberto Gismanti.
Keywords: Beni Biological Station (Bolivia); La Amistad (Costa Rica); Biological diversity conservation -- Brazil; Deforestation -- Brazil; Rainforests -- Conservation -- Brazil; Biological diversity conservation -- Bolivia; Biological diversity conservation -- Costa Rica; Biological diversity conservation -- Panama